FPGA‐assisted state‐of‐polarisation generation for polarisation‐encoded optical communications - Muga, Nelson J. (2020)
This study presents a theoretical model for polarisation manipulation using electronic polarisation controllers (EPCs) based on fibre squeezing. A method to calculate the EPC configuration in order to transform between two arbitrary states of polarisation (SOP) is presented. After, a technique to deterministically generate four SOPs for use in polarisation-encoded quantum communication systems is proposed. Moreover, the effectiveness of the proposed technique is experimentally assessed through the generation of two pairs of orthogonal SOPs. The experimental implementation used an field programmable gate array (FPGA) board to electrically control the four waveplates of the EPC, reaching a rate of 500 qubit/s. Results show that this polarisation generation process is intrinsically stable, demonstrating its potential for practical implementations of polarisation-encoding quantum key distribution systems using the BB84 and B92 protocols.